IMPACT OF PROTEAN CAREER ORIENTATION ON ACADEMICS' CAREER SUCCESS: THE MEDIATING ROLE OF PSYCHOLOGICAL CAPITAL - Yousif, Mohammed Mustafa Mohammed; Mohd Nor, Mohammad Nazri; Omar, Safiah (Journal of Technology Management and Business, 2019)
Most people seek success in their career due to the prominent role of career in shaping their lifestyle from the first day they started working with organization. However, some people feel unsuccessful in their career. Hence. the main purpose of this study is to investigate the mediating role of psychological capital (PsyCap) between protean career orientation (PCO) and career success. Further, this study is quantitative in nature based on primary data which were collected from full-time lecturers teaching in Sudanese public universities. Out of the 250 self-administrated questionnaires, 209 were returned for final analysis. The data obtained were analyzed by using the Smart-PLS 3.2.6 software techniques. Besides the context of this study, another uniqueness of this study was with the model in which career success was assessed as a formative construct. However, in the past studies, it was assessed as a reflective construct. The findings indicated that PsyCap was not only an important predictor of career success in the academic atmosphere, but it also played a positive mediator between PCO and career success. The paper closed with implications and conclusion. Keywords: Academics’ career success, psychological capital, positive psychology, and protean career orientation.